The monetary base properly extended - Nikolaus K. A. Läufer (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1982)
The available concepts of an extended monetary base are seriously defective. They provide equal measurements for differently sized impulse forces of monetary policy and different measurements for equally sized impulse forces of monetary policy. A new concept is suggested that allows to avoid these measurement errors. It is shown that an extended base with a minimum of defects may be obtained by subtracting from the ordinary monetary base all required reserves. Thus, the best extension of the monetary base turns out to be a simple reduction. The view expressed in this paper may also be interpreted to be a prescription for the appropriate choice of. the base period in the construction of an extended base as suggested by the St.Louis Federal Reserve Bank. With such, a choice changes in the structure of reserve requirements as under the Monetary Control Act of 1980 would not cause problems and would not require special actions and revisions for a proper extension (adjustment) of the monetary base.
Keywords: 330